The Effect Ratio of Star Fruit Pulp with Aloe vera Pulp and Sodium Benzoate Concentration on the Quality of Pulpy Star Fruit Juice - Johana Novita Paulina Purba; Sentosa Ginting; Ismed Suhaidi (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The research was aimed to determine the best product of pulpy star fruit juice obtained from a combination of the best treatment from star pulp with aloe vera pulp and sodium benzoate concentration. The research had been performed using factorial completely randomized design, with two factors i.e : the ratio of star fruit pulp and aloe vera pulp (P) : 90%;10%, 80%:20%, 70%:30%, 60%:40%, and sodium benzoate concentration (N) : 0,025%, 0,050%, 0,075%, 0,100%. Parameters analyzed were total soluble solid (oBrix), total acid, vitamin C content, degree of acidity (pH), viscosity, and organoleptic values (flavor and taste). The result showed that the ratio of star fruit pulp with aloe vera pulp and sodium benzoate concentration had highly significant effect on total soluble solid (0Brix), total acid, vitamin C content, degree of acidity (pH), viscosity, and organoleptic values (flavor and taste). The interaction of  two factors had significant effect on total soluble solid (oBrix). The ratio of star fruit pulp with aloe vera pulp of  90%:10% and sodium benzoate concentration of 0,100% produced the best quality of pulpy star fruit juice. Keyword : Fruit pulp, juice, sodium benzoate